Glycaemic, cardiorenal, and lipid parameters associated with SGLT2 inhibitors use in Indonesian patients with type 2 diabetes: 12-month multicenter real-world study - Fonny Cokro; Rani Sauriasari; Dicky Levenus Tahapary; Heri Setiawan; Christian Tricaesario; Nurul Hidayati; William Djauhari; Jimmy Tandradynata; Sidartawan Soegondo (PLoS ONE, 2026)
Background Sodium-glucose cotransporter-2 inhibitors (SGLT2is) have demonstrated efficacy in glycaemic control and cardiorenal protection across multiple meta-analyses. However, their applicability to the Indonesian population remains uncertain due to demographic, lifestyle, and healthcare disparities. This study aims to evaluate the effectiveness of SGLT2is in managing metabolic control, cardiorenal risk factors, and their safety relative to non-SGLT2is in the T2DM population in Indonesian real clinical settings. Methods This study applied a multicenter retrospective cohort design, enrolling adult Indonesian T2DM patients who had received treatment for at least 12 months. Intragroup paired analysis and intergroup comparative studies were performed regarding metabolic control, cardiorenal, and safety parameters. Results A total of 638 patients were included, with 319 patients contributing to paired analyses. In paired data analysis, SGLT2is significantly improved HbA1c, fasting plasma glucose (FPG), body weight, body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), lipid profile, and atherosclerotic cardiovascular disease (ASCVD) risk (p < 0.05). Compared to non-SGLT2is, SGLT2is are associated with greater reductions in HbA1c, FPG, body weight, BMI, and SBP. Although no intergroup differences were observed in other parameters, adjusted analyses revealed additional benefits of SGLT2is in lowering low-density lipoprotein (LDL) cholesterol and maintaining estimated Glomerular Filtration Rate (eGFR), though SBP effects became nonsignificant. No major safety signals were observed. Conclusion These findings support the use of SGLT2is as effective agents for improving glycaemic control, body weight, blood pressure, lipid profile, and ASCVD risk in Indonesian patients with T2DM. Further studies are warranted to clarify their safety, long-term renal effects, and to explore the comparative effects of individual SGLT2is and dosing strategies.